Surgical Volume and Postoperative Complications of Acromioclavicular Joint Separations: Analysis of the ABOS Part II Examination. Issue 13 (November 2018) - Hippensteel, K.J.; Brophy, Robert; Smith, Matthew; Wright, Rick
Background: High-grade acromioclavicular (AC) joint separations are relatively rare injuries that are often treated surgically, yet more information is needed about the risks of various surgical procedures in terms of considering and counseling patients regarding operative versus nonoperative treatment. Purpose: To calculate whether the volume of surgical treatment of AC joint separations increased over a recent 12-year period; to examine the nature and frequency of complications, reoperations, and readmissions associated with these procedures; and to assess whether patient- and surgeon-specific factors or surgical technique affected these rates. Study Design: Cross-sectional study; Level of evidence, 3. Methods: The American Board of Orthopaedic Surgery (ABOS) database for orthopaedic surgeons taking the Part II examination was reviewed from 2005 to 2016 to identify surgical treatment of AC joint separations. The authors calculated the percentage of all surgical cases in the ABOS database and rates of complications, reoperations, and readmissions. Association of these sequelae with patient- and surgeon-specific factors and surgical techniques was assessed. Results: There was no difference in the number or percentage of cases per year over the study period. There was an overall complication rate of 24.5%, a reoperation rate of 7.3%, and a readmission rate of 1.9%. Patients ≥40 years of age had significantly higher complication, reoperation, and readmission rates as compared with patients <40 years of age. There were significant differences in complication, reoperation, readmission, and displacement rates dependent on the type of surgical procedure performed. The highest complication rates were seen with open suspensory fixation, screw fixation, open reduction internal fixation, and arthroscopic coracoclavicular ligament repair or reconstruction. The highest reoperation rates were seen with screw fixation, open reduction internal fixation, and open suspensory fixation. Conclusion: The volume of surgical treatment for AC joint separations did not change significantly over the study period. Complication, reoperation, and readmission rates were dependent on the type of surgical procedure performed and patient age. This information should assist surgeons in discussing risks when considering and counseling patients regarding operative versus nonoperative treatment.